Upaya Pengaruh Penggunaan Media Manipulatif Berhitung terhadap Kemampuan Mengenal Konsep Bilangan dada Anak Usia 4-5 Tahun - Asih Trianti; Bakti Toni Endaryono (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2020)
This study aims to determine the effect of counting manipulative media on the ability to recognize the concept of numbers in children aged 4-5 years in Penang Kenanga Hati Bunda, with variable (x) the effect of using counting manipulative media and variable (y) The ability to recognize number concepts in children aged 4 -5 years, the method in this study is to use descriptive qualitative methods by collecting data through interviews, documentation, observation and questionnaires with respondents, students, parents and teachers with 10 questions, the results of this study are in Paud Kenanga Hati Bunda already implemented with both reached 80%, this is marked by the child's ability to recognize numbers, which includes giving examples of the ability to practice counting, motivation, reward, correction and guidance. Keywords; manipulative media, numeracy skills, number concepts